(untitled) (Canadian Medical Education Journal, 2025)
Implication Statement Point-of-care ultrasound (POCUS) is becoming increasingly used in primary care and has the potential to be accessible, reliable, and indispensable. However, few family medicine residency programs offer training in POCUS. Therefore, we have developed a two half-day training program for family medicine residents to help them acquire more knowledge in this area and improve their confidence. The sessions were highly appreciated by the residents. This project could pave the way for the development of a standardized curriculum and its widespread dissemination.